Infección vaginal por el virus del papiloma humano - Milgrom P, Drs. Rosara; Fuenmayor M, Teresa; Rincón M, Francisco; Aguilar de Petit, Olivia; Santimone B, Mario (Gaceta Médica de Caracas, 2021)
Se estudiaron 25 mujeres con lesiones papilares de vagina en el Servicio de Ginecología y Reproducción Humana del Hospital Carlos J Bello de la Cruz Roja Venezolana, entre octubre de 1996 y diciembre de 1997. Twenty-five women with a papillary lesion of vagina were studied at the Service of Gynecology and Human Reproduction from the “Carlos J Bello” Hospital, Venezuelan Red Cross, from October 1996 until December 1997.